Free Shipping: When E-Commerce Regulations Exceed the Limits of Authority - Muh. Akbar Fhad Syahril (Jurnal Litigasi Amsir, 2025)
This study analyzes the implications of the overlapping authority between the Ministry of Communication and Digital (Komdigi) and the Ministry of Trade (Kemendag) in regulating free shipping programs in the e-commerce sector in Indonesia. Through a normative juridical approach and an analysis of legal theories of attribution, delegation, and ultra vires, this study finds that regulatory dualism between the two ministries has created legal uncertainty, market distortions, and obstacles to the growth of the digital economy. Empirical data shows increased complaints from business actors and consumers due to uncoordinated policies. This study recommends regulatory harmonization and the establishment of a transparent and integrated national digital legal framework to support legal certainty and consumer protection in the digital economy era.